Simulação sequencial de atributos diagnósticos do solo - Silva, Alessandra F. da; Pereira, Maria J.; Zimback, Celia R. L. [UNESP]; Landim, Paulo M. B. [UNESP]; Soares, Amilcar (Univ Federal Campina Grande, 2015)
The sequential simulation generates a set of equiprobable images with the same spatial variability of the experimental values. The aim of this study was to determine the spatial dependence of the diagnostic attributes of soil and use the sequential simulation to characterize the probability distribution of the location attribute and verify areas of uncertainty. The study area, with 1200.32 ha, was the experimental farm Edgardia belonging to the Faculdade de Ciencias Agronomicas da Universidade Estadual Paulista, Botucatu, SP. The soil properties were obtained from a sampling grid of 90 points. From the spatial dependency model the direct sequential simulation and sequential indicative simulation was performed. Soil attributes show spatial dependence with different directions to lesser and greater range. The direct sequential simulation and sequential indicative simulation allowed the evaluation of the spatial distribution of the uncertainty of continuous and categorical variables and soil, which can be used to define, with more confidence, soil classes and to integrate studies of sample planning in places where the variability is most pronounced.

A simulação sequencial gera um conjunto de imagens equiprováveis com a mesma variabilidade espacial dos valores experimentais. O objetivo deste estudo foi analisar a dependência espacial dos atributos diagnósticos do solo e aplicar a simulação sequencial para caracterizar a distribuição de probabilidade local dos atributos e verificar as zonas de incerteza. A área de estudo, com 1.200,32 ha, compreende a fazenda experimental Edgardia da Faculdade de Ciências Agronômicas da Universidade Estadual Paulista, Botucatu, SP. Os atributos do solo foram obtidos a partir de uma grade de amostragem de 90 pontos. A partir do modelo de dependência espacial foi realizada a simulação sequencial direta e a simulação sequencial indicativa. Os atributos do solo apresentaram dependência espacial com diferentes direções para menor e maior alcance. A simulação sequencial direta e a simulação sequencial indicativa possibilitaram a avaliação da incerteza da distribuição espacial das variáveis categóricas e contínuas do solo a qual pode ser utilizada para definir, com mais confiança, as classes de solo e para integrar estudos de planejamento amostral em locais em que a variabilidade é mais acentuada.
Sequential simulation of diagnostic soil attributes
Keywords: Direct sequential simulation; Sequential indicative simulation; Categorical variable